1997
DOI: 10.1152/ajprenal.1997.273.4.f507
|View full text |Cite
|
Sign up to set email alerts
|

PGE2-mediated cytoprotection in renal epithelial cells: evidence for a pharmacologically distinct receptor

Abstract: Although the exact mechanism of prostaglandin E2(PGE2)-mediated cytoprotection has not been elucidated, its ability to induce cytoprotection in cell culture suggests this action occurs at the cellular level. The present studies were conducted to determine whether PGE2 induces protection against 2,3,5-(trisglutathion- S-yl)-hydroquinone [2,3,5-(trisglutathion- S-yl)-HQ]-mediated cytotoxicity in a renal proximal tubule epithelial cell line (LLC-PK1) and to delineate the cellular and molecular mechanisms associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
42
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 30 publications
(44 reference statements)
4
42
0
Order By: Relevance
“…Recently, PGE 2 was reported to initiate a positive feedback loop via EP 4 in the podocyte signaling network, activated by increased glomerular capillary pressure, which could be detrimental to podocyte health and glomerular filtration barrier integrity. 17 However, other studies have suggested that PGE 2 serves a cytoprotective function in renal epithelial cells 18,19 In other cell types, PGE 2 has been shown to promote cell survival, cell growth, migration, invasion, and angiogenesis. 20,21 In this regard, podocytes from COX-2-knockout mice were found to exhibit significant apoptosis even under basal conditions, suggesting that COX-2-derived prostaglandins also may serve a trophic cytoprotective function.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, PGE 2 was reported to initiate a positive feedback loop via EP 4 in the podocyte signaling network, activated by increased glomerular capillary pressure, which could be detrimental to podocyte health and glomerular filtration barrier integrity. 17 However, other studies have suggested that PGE 2 serves a cytoprotective function in renal epithelial cells 18,19 In other cell types, PGE 2 has been shown to promote cell survival, cell growth, migration, invasion, and angiogenesis. 20,21 In this regard, podocytes from COX-2-knockout mice were found to exhibit significant apoptosis even under basal conditions, suggesting that COX-2-derived prostaglandins also may serve a trophic cytoprotective function.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reasonable amounts of the EP2 selective agonist butaprost (Km approximately 100 nM; (40)) do not affect basolateral organic uptake rate, neither after 10 min nor acutely. The EP selective agonists used were shown to act not only in rodents but also in cells from pigs (41) and humans (15). Thus, their pharmacologic profile seems not to be strictly species dependent.…”
Section: Discussionmentioning
confidence: 99%
“…They have sequentially characterized the signaling pathways of renal proximal tubule (LLC-PK 1 cells) protection with DDM-PGE 2 in previous studies. They showed that DDM-PGE 2 protects against necrosis via thromboxane receptor activation through a PKC signal transduction pathway coupled to NF-B (20). They also showed the upregulation of several potential cytoprotective proteins, including glucose-regulated protein 78 (Grp78).…”
mentioning
confidence: 99%